Malaysia: Constitution (Amendment) Act 1983 And Constitution (Amendment) Act 1984 - Hickling, R.H. (Journal of Malaysian and Comparative Law, 2019)
Between August 1983 and January 1984 an extraordinary constitutional drama was staged in Malaysia. On 1 August 1983 a Constitutional (Amendment) Bill was given a first reading; before the bill reached the statute book as an Act of Parliament, a written undertaking was given by the Prime Minister to the Rulers, concerning the Bill, in consequence of which a second amendment Act was enacted: the second Act in fact reversing much of what the first Act was set out to achieve.